Enablers of Innovation Performance among Malaysian Small Medium Enterprises toward Industrial Revolution 4.0 - Teh, Shan Shan; Kee, Daisy Mui Hung (International Journal of Psychosocial Rehabilitation, 2020)
Innovation is a concept that has received much attention in recent years. Innovation is one of the critical factors for organizational success and competitiveness. In Malaysia, innovative behavior is still at the infancy stage, especially among SMEs. The innovation rate in Malaysia is also not reaching full potential yet. Although industrial revolution 4.0 is gaining popularity, SMEs remain relatively unaware of the importance of innovation. Therefore, a quantitative study will be conducted among Malaysian SMEs on how to improve innovation performance. The social media and entrepreneurial orientation are the enablers of innovation performance proposed in the present study. Social media is a tool used to interact with customers to acquire useful information in the development stage. Moreover, with the entriepreneurial orientation possessed by the organization, it can lead the organization toward innovation. Besides the two enablers of innovation performance, open innovation is also proposed as a mediator. Open innovation allows the organization to explore outside knowledge and exploit internal resources to stay competitive. As such, open innovation is mediating social media and entrepreneurial orientation toward a better innovation performance among Malaysian SMEs in the era of industrial revolution 4.0. The present study also added knowledge to the theory of the knowledge-based view.